Prompt microwave-assisted synthesis of carbon coated Si nanocomposites as anode for lithium-ion batteries - Uctepe, Ali; Demir, Emrah; Tekin, Burak; Dursun, Burcu; Ozturk, Osman; Sel, Ozlem; Demir-Cakan, Rezan (Elsevier, 2020)
Hard carbons derived from glucose and glucosamine are synthesized via microwave-assisted hydrothermal carbonization (HTC) and subsequent pyrolysis treatment to be used as anode materials for lithium-ion batteries (LIBs). Related to the limited lithium ion intercalation to graphite (LiC6) resulting relatively low theoretical capacity (372 mAh/g), silicon is considered as one of the most appealing anode materials for LIBs by exhibiting very high theoretical capacity (3578 mAh/g, based on Li15Si4). However, silicon suffers from huge volume expansion during intercalation of lithium ions which causes rapid capacity fading. One of the most practical strategy to suppress this problem is to coat the silicon nanoparticles with carbonaceous materials. Herein, silicon is coated via microwave-assisted hydrothermal carbonization method in the presence of glucose or glucosamine which are then further pyrolyzed at 750 degrees C to obtain silicon-carbon composite anodes. Composite containing glucosamine (Si-GA-C-750) enables N-doped carbon evidenced by EDX and XPS analyses which contributes to obtain much enhanced electrochemical properties than that of glucose containing composite (Si-G-C-750). Additionally, higher Li+ diffusion coefficient and smaller resistance values attest the advantageous nature of the N-doped anode material.
Keywords: Microwave synthesis; Lithium-ion batteries; Silicon; Carbon; Hydrothermal Carbonization